Analysis Of The Implementation Of Internal Audit, Risk Management, And Customer Eligibility In Minimizing Problems In Financing Risks At Bank Sumut Syariah Kcp Kisaran - Alfarezzi, Ahmad; Sugianto, Sugianto; Anggraini, Tuti (UNIVERSITAS PAKUAN, 2024)
This study aims to determine